PERSEPSI GEN Z TERHADAP SERIAL DRAMA KOREA CELEBRITY - Andika Pratama; Ali Nupiah (KINEMA: Jurnal Komunikasi dan Penyiaran, 2025)
This study aims to explore Gen Z's perception of Korean dramas, especially those involving celebrities in the Korean series industry. Along with the rapid development of the Korean Wave phenomenon, Korean dramas have become an important part of media consumption, especially for the younger generation who grew up in the digital era. This study focuses on how Gen Z in Batusangkar City views and interacts with Korean dramas, as well as the influence of Korean series celebrities in shaping their perceptions of the culture. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. Observations were conducted in the field to observe audience interactions with Korean dramas, while interviews were used to explore individual opinions on how they interpret and respond to messages conveyed through the drama and celebrities. The data obtained were analyzed descriptively to describe the views and influence of Korean culture on Gen Z's mindset and behavior. The results of the study show that Gen Z has a strong interest in Korean dramas, which is not only influenced by the storyline, but also by the image of the celebrities who appear in the series. In addition, perceptions of Korean celebrities are also influenced by factors such as internal and external factors. This study provides deeper insight into how Gen Z understands and consumes entertainment media, as well as how Korean celebrities play a role in shaping their perceptions of Korean culture.